Tragic Curse, or Messianic Hope? Reading Genesis 3:16 in Light of Genesis 3:15 - Doukhan, Jacques (Religions, 2024)
In this paper, it will be shown that Genesis 3:16 parallels the Messianic prophecy of Genesis 3:15 with which it also shares significant linguistic links and literary features. From this literary observation, it will be established that the two key words “desire” and “rule” have a positive significance which is further supported by the literary and syntactical construction of the sentences. The positive understanding of Genesis 3:16 in the light of Genesis 3:15 will also be reinforced and illuminated by the comparative analysis with the parallel text of Genesis 4:7. Rather than proclaiming the tragic “curse” of the subordinated woman in her relationship with man, the connection of Genesis 3:16 with Genesis 3:15 brings a message of blessing in the perspective of redemption.